High‐temperature‐resistant polymer gel system with metal–organic mixed cross‐linking agents. Issue 29 (16th April 2015) - Zhang, Xiaoyun; Zhang, Sisi; Li, Liang; Wu, Ruonan; Liu, Dongming; Wu, Jihui; Wu, Wei
ABSTRACT A high‐temperature (200°C)‐resistant polymer gel system was developed from partially hydrolyzed polyacrylamide (HPAM), chromium lactate (CrL), and water‐soluble phenol/formaldehyde resin (WPF) mixed cross‐linkers. Rheological measurements indicated that the gelation process of the gel system could be divided into four successive steps: induction, first cross‐linking with metal cross‐linker, secondary cross‐linking with organic cross‐linker, and stabilization. Effects of various parameters that affect the gelation time and gel strength including polymer concentration, cross‐linker concentration, salinity, pH, and the gelation temperature were evaluated. Gelant formulated with 0.5 wt % HPAM, 0.1 wt % CrL, and 0.9 wt % WPF and treated at 80°C for 48 h showed sufficient gelation time, high rigidity, and good thermal stability. Morphology observation by scanning electron microscopy (SEM) and atomic force microscopy (AFM) revealed that the gel had compact network microstructure. A cross‐linking mechanism for the gel system was proposed based on the gelation process and experimental results. © 2015 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 2015, 132, 42261.